(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
This paper aims to provide a systemic vision of the role and specifics of a Covid-19 contact-tracing mobile application, which can be presented as a data-driven mobile application for citizens in urban data management processes and is essential for a sustainable urban ecosystem to inform the user about contact with a potentially infected person. The study aims to reveal the behaviour of adults when using such an application. We also attempt to discover how the Covid 19 pandemic has changed communication and why users use mobile phones and their features, such as Bluetooth and GPS. The research focused on Slovenia and was conducted during the Covid-19 pandemic in April 2021. Five hundred adults were surveyed. The mixed-method survey investigates the determinants of adult citizens’ behaviour in the Republic of Slovenia concerning the #Ostanizdrav application from three perspectives (installed app, activated app, and app used to report infection). In addition, the study examines the barriers and levers to using a contact tracing application to combat the pandemic in Slovenia. The second part of the study involves developing a Deep Learning-based predictive model trained on the data collected due to the survey.